Iridaceae - Goldblatt, Peter; Manning, J.C. (African Biodiversity & Conservation, 2012)
Notes on Moraea subg. Visciramosa (Iridoideae), including the new species Moraea saldanhensis from the Atlantic coast of South Africa, recognition of M. inconspicua subsp. namaquensis, and pollination biology in M. rivulicola.